Rechargeable lithium battery

By designing appropriate porosity in the positive electrode and controlling ion resistance in the negative electrode of the rechargeable lithium battery, the problem of poor fast charging characteristics caused by lithium iron phosphate oxides has been solved, achieving high safety, high capacity and fast charging performance.

CN120978153APending Publication Date: 2025-11-18SAMSUNG SDI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510416849.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-03-06
Filing Date
2025-04-03
Publication Date
2025-11-18

AI Technical Summary

Technical Problem

Existing rechargeable lithium batteries using lithium iron phosphate oxides as the positive electrode active material suffer from reduced positive electrode porosity and increased negative electrode ionic resistance, resulting in poor fast charging characteristics.

Method used

By designing pores of 0.6μm to 1μm and a porosity of greater than or equal to 23% in the positive electrode, and controlling the ion resistance to be less than or equal to 20Ωcm2 in the negative electrode, combined with appropriate electrode active material layer thickness, mixture density and pore size, high safety and high capacity are ensured while achieving fast charging characteristics.

Benefits of technology

This achieves improved fast-charging performance of rechargeable lithium batteries while ensuring high safety and high capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120978153A_ABST
    Figure CN120978153A_ABST
Patent Text Reader

Abstract

Disclosed is a rechargeable lithium battery including: a positive electrode including a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector and including a lithium iron phosphate-based positive electrode active material; a negative electrode including a negative electrode current collector and a negative electrode active material layer on the negative electrode current collector and including a carbon-based negative electrode active material; and an electrolyte. The positive electrode includes pores having a size of about 0.6 [mu] m to about 1 [mu] m, the positive electrode having a porosity of greater than or equal to about 23%, and the negative electrode having an ionic resistance of less than or equal to about 20 [Omega] cm2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] A rechargeable lithium battery has been disclosed. Background Technology

[0002] Rechargeable lithium batteries are portable, typically achieve high energy density, and are widely used as power sources for mobile information terminals such as smartphones and laptops. Rechargeable lithium batteries, with their high safety and high capacity, are advantageous as power sources for applications such as hybrid or electric vehicles, or as energy storage.

[0003] In addition to high capacity and high safety, rechargeable lithium batteries that also ensure fast charging characteristics are advantageous; therefore, low-cost lithium iron phosphate oxides are sometimes used as positive electrode active materials. These lithium iron phosphate oxides have a stable structure and, like using phosphate materials themselves as flame retardants, possess desirable or advantageous thermal stability.

[0004] Assuming lithium iron phosphate oxides are used as the positive electrode active material, high capacity can be achieved by increasing the density of both the positive and negative electrode mixtures. However, a higher positive electrode mixture density results in a more densely packed positive electrode active material, reducing the porosity and pore size of the positive electrode, which may hinder fast charging. Similarly, a higher negative electrode mixture density may increase the ionic resistance of the negative electrode, also potentially hindering fast charging.

[0005] Therefore, in order to achieve high safety, the positive and negative electrodes should be designed to ensure high capacity and fast charging characteristics while using this lithium iron phosphate oxide as the positive electrode active material. Summary of the Invention

[0006] Some example embodiments include rechargeable lithium batteries that can ensure both higher safety and higher capacity while also providing fast charging characteristics.

[0007] A rechargeable lithium battery according to some example embodiments includes: a positive electrode comprising a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector and comprising a lithium iron phosphate-based positive electrode active material; a negative electrode comprising a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector and comprising a carbon-based negative electrode active material; and an electrolyte. The positive electrode includes pores with a size of about 0.6 μm to about 1 μm and has a porosity greater than or equal to about 23%, and the negative electrode has a porosity less than or equal to about 20 Ωcm. 2 The ionic resistance.

[0008] According to some example embodiments, rechargeable lithium batteries can advantageously ensure fast charging characteristics while ensuring higher safety and higher capacity. Attached Figure Description

[0009] Figures 1 to 4 This is a schematic diagram illustrating a rechargeable lithium battery according to some example embodiments. Detailed Implementation

[0010] Hereinafter, exemplary embodiments will be described in detail so that those skilled in the art can readily implement them. However, this disclosure may be implemented in many different forms and is not to be construed as limited to the exemplary embodiments set forth herein.

[0011] The terminology used herein describes exemplary embodiments only and is not intended to limit this disclosure. Unless the context clearly specifies otherwise, singular expressions include plural expressions.

[0012] As used herein, “combination of” describes mixtures, laminates, complexes, copolymers, alloys, blends, reactants, etc. of the components.

[0013] It should be understood here that terms such as “comprising,” “including,” or “having” are intended to specify the presence of the features, quantities, steps, elements, or combinations thereof embodied, but these terms do not preclude the possibility of the presence or addition of one or more other features, quantities, steps, elements, or combinations thereof.

[0014] In the figures, for clarity, the thickness of layers, films, panels, regions, etc., may be exaggerated, and the same reference numerals denote the same elements throughout the specification. It will be understood that when an element such as a layer, film, region, or substrate is referred to as being "on" another element, it may be directly on said other element, or an intervening element may be present. Conversely, when an element is referred to as being "directly on" another element, no intervening element is present.

[0015] Furthermore, the term "layer" here includes not only the shape formed on the entire surface when viewed from a plane, but also the shape formed on a portion of the surface.

[0016] The average particle size can be measured by methods such as those using a particle size analyzer, or by means of transmission electron microscopy (TEM) or scanning electron microscopy (SEM) images. Alternatively, the average particle size value can be obtained by measuring using dynamic light scattering, performing data analysis, counting the number of particles in each particle size range, and calculating from there. Unless otherwise defined, the average particle size can describe the diameter (D) of particles having a cumulative volume of 50% of the particle size distribution. 50As used herein, unless otherwise defined, the average particle size describes the diameter (Dsize) of particles representing 50% of the total volume of a particle size distribution obtained by randomly measuring the size (diameter or major axis length) of approximately 20 particles in a scanning electron microscope image. 50 ).

[0017] Here, "or" will not be interpreted as having an exclusive meaning; for example, "A or B" is interpreted as including "A", "B", "A+B", etc.

[0018] The term "metal" is interpreted as encompassing common metals, transition metals, and metalloids (semi-metals).

[0019] When the terms “about” or “basic” are used in conjunction with numerical values ​​in this specification, it means that the relevant numerical value includes a tolerance of ±10% around the stated value. When a range is specified, the range includes all values ​​within that range, such as increments of 0.1%.

[0020] In some example embodiments, a rechargeable lithium battery that ensures high capacity and fast charging characteristics is provided by using lithium iron phosphate-based positive electrode active materials to ensure safety and price competitiveness, while controlling the thickness, mixture density, porosity, pore size and ionic resistance of the negative electrode within appropriate ranges.

[0021] The following sections will describe the positive electrode, negative electrode, electrolyte, and rechargeable lithium battery.

[0022] positive electrode According to some example embodiments, the positive electrode includes a lithium iron phosphate-based positive electrode active material. For example, the positive electrode includes a positive electrode current collector and a positive electrode active material layer located on the positive electrode current collector and including the lithium iron phosphate-based positive electrode active material.

[0023] For example, lithium iron phosphate positive electrode active materials can be represented by chemical formula 1 or chemical formula 2.

[0024] Chemical Formula 1: Li a1 Fe (1-x1) M 1 x1 PO4 In chemical formula 1, 0.90 ≤ a1 ≤ 1.5, 0 ≤ x1 ≤ 0.4, and M 1The elements are Al, B, Ca, Ce, Cr, Cu, La, Mg, Mn, Mo, Nb, Ni, Si, Sn, Sr, Ti, V, W, Y, Zn, Zr, or combinations thereof. Here, 0.90 ≤ a1 ≤ 1.5, for example, 0.90 ≤ a1 ≤ 1.2, or 0.95 ≤ a1 ≤ 1.1. Furthermore, 0 ≤ x1 ≤ 0.4, 0 ≤ x1 ≤ 0.3, 0 ≤ x1 ≤ 0.2, 0 ≤ x1 ≤ 0.1, or 0 ≤ x1 ≤ 0.05.

[0025] Chemical formula 2: Li a2 Mn x2 Fe (1-x2-y2) M 2 y2 PO4 In chemical formula 2, 0.90 ≤ a² ≤ 1.5, 0.1 ≤ x² ≤ 0.9, 0 ≤ y² ≤ 0.9, and M 2 The elements are Al, B, Ca, Ce, Cr, Cu, La, Mg, Mo, Nb, Ni, Si, Sn, Sr, Ti, V, W, Y, Zn, Zr, or combinations thereof. Here, 0.90 ≤ a² ≤ 1.5, or for example, 0.90 ≤ a² ≤ 1.2, or 0.95 ≤ a² ≤ 1.1. Furthermore, 0.1 ≤ x² ≤ 0.9, 0.3 ≤ x² ≤ 0.9, or 0.4 ≤ x² ≤ 0.8, and 0 ≤ y² ≤ 0.4, 0 ≤ y² ≤ 0.3, 0 ≤ y² ≤ 0.2, 0 ≤ y² ≤ 0.1, or 0 ≤ y² ≤ 0.05.

[0026] According to some example embodiments, the positive electrode can ensure price competitiveness, heat resistance, and high safety by including lithium iron phosphate-based positive electrode active materials.

[0027] Positive electrode active materials, including lithium iron phosphate compounds, are in particulate form, and the average particle size (D) of the particles is... 50 The particle size can be from about 0.01 μm to about 4 μm, for example, from about 0.1 μm to about 3.5 μm, from about 0.2 μm to about 3 μm, from about 0.3 μm to about 2.5 μm, from about 0.4 μm to about 2 μm, or from about 0.6 μm to about 1.5 μm. The lithium iron phosphate positive electrode active material can be in the form of secondary particles formed by aggregates of multiple primary particles, in the form of single particles, or a combination thereof. Secondary particles can be or include aggregates of primary particles with a size of about 10 nm to about 400 nm, and the average particle size of the secondary particles can be from about 2 μm to about 15 μm. The average particle size of a single particle can be from about 10 nm to about 900 nm or from about 100 nm to about 300 nm. Here, the average particle size can be obtained by measuring the size of about 20 random particles using an electron microscope to obtain the particle size distribution, and accumulating the size of particles representing 50% by volume (D...) 50() is used as the average particle size.

[0028] Lithium iron phosphate positive electrode active materials may further include a carbon coating on the particle surface. The carbon coating can improve the conductivity of the lithium iron phosphate positive electrode active material and reduce the resistance of the positive electrode. For example, the carbon coating can be derived from at least one raw material, such as or including at least one of the following: polymers of glucose, sucrose, lactose, starch, oligosaccharides, polyoligosaccharides, fructose, cellulose, furfuryl alcohol, block copolymers of ethylene and ethylene oxide, vinyl resins, cellulose resins, phenolic resins, asphalt resins, and tar resins. For example, the raw material can be placed on the surface of the lithium iron phosphate positive electrode active material particles and then fired to form the carbon coating.

[0029] Based on a 100wt% positive electrode active material layer, the amount of lithium iron phosphate positive electrode active material can be approximately 60wt% to approximately 99.9wt%, approximately 70wt% to approximately 99.8wt%, approximately 80wt% to approximately 99wt%, or approximately 90wt% to approximately 98wt%. By including lithium iron phosphate positive electrode active material in the positive electrode in the above amounts, fast charging performance can be improved while ensuring price competitiveness, capacity, and safety.

[0030] The positive electrode can ensure price competitiveness and high safety by including lithium iron phosphate positive electrode active materials, and high capacity and fast charging characteristics can be ensured by properly adjusting the thickness, mixture density, porosity and pore size of the positive electrode.

[0031] The positive electrode according to some example embodiments includes pores with a size of about 0.6 μm to about 1 μm. In another example, the pore diameter of the positive electrode may be greater than or equal to about 0.61 μm, greater than or equal to about 0.62 μm, or greater than or equal to about 0.63 μm, and less than or equal to about 0.95 μm, less than or equal to about 0.9 μm, less than or equal to about 0.89 μm, less than or equal to about 0.88 μm, less than or equal to about 0.87 μm, or less than or equal to about 0.86 μm. Here, the size of the pores in the positive electrode can be measured by mercury intrusion porosimetry. Specifically, a mercury porosimeter can be used to inject mercury into the pores of the sample by applying a pressure of 360,000 to 361,727 psia, and the total pore volume, pore diameter and distribution, and pore surface area can be measured based on the amount of mercury injected. Furthermore, if the pore cross-section is circular, the pore size can be described as the diameter; if the pore cross-section is elliptical, the pore size can be described as the length of the major axis; and if the pore cross-section is irregular, the pore size can be described as the length of the longest side. Pores with a size of approximately 0.6 μm to approximately 1 μm can be formed in the positive electrode by appropriately adjusting the particle size and physical properties of the lithium iron phosphate-based positive electrode active material, the formation and drying conditions of the positive electrode active material layer, and the pressing conditions of the positive electrode. When the positive electrode including the lithium iron phosphate-based positive electrode active material includes pores with a size of approximately 0.6 μm to approximately 1 μm, fast charging characteristics can be improved. Here, the pore size can refer to the average pore size. More specifically, the pore size in the positive electrode can refer to the pore size in the positive electrode active material layer.

[0032] The porosity of the positive electrode according to some example embodiments can be greater than or equal to about 23%. In another example, the porosity of the positive electrode can be greater than or equal to about 23.5%, greater than or equal to about 24%, greater than or equal to about 24.5%, or greater than or equal to about 25%, and less than or equal to about 50%, less than or equal to about 45%, less than or equal to about 40%, less than or equal to about 35%, or less than or equal to about 33%. The porosity of the positive electrode can be measured by mercury intrusion porosimetry. Specifically, a mercury porosimeter can be used to inject mercury into the pores of the sample by applying a pressure of 360,000 to 361,727 psia, and the total pore volume, pore size and distribution, and pore surface area can be measured based on the amount of mercury injected. The porosity of the positive electrode can be adjusted to be greater than or equal to about 23% by appropriately adjusting the particle size and physical properties of the lithium iron phosphate positive electrode active material, the formation and drying conditions of the positive electrode active material layer, and the pressing conditions of the positive electrode to reduce the density of the positive electrode mixture.

[0033] The positive electrode includes lithium iron phosphate-based positive electrode active materials, and when the size and porosity of the pores included in the positive electrode are within the above-mentioned range, high stability, high capacity and fast charging characteristics can be ensured.

[0034] The positive electrode active material layer may optionally further include other types of positive electrode active materials besides lithium iron phosphate positive electrode active materials.

[0035] Other types of positive electrode active materials can be used without restriction, as long as they are common positive electrode active materials in rechargeable lithium batteries. For example, compounds capable of reversibly inserting and deintercalating lithium (lithium-intercalation compounds) can be used. For instance, one or more composite oxides of lithium and metals such as or including at least one of cobalt, manganese, nickel, and combinations thereof can be used. For example, the positive electrode active material can include lithium transition metal composite oxides, and examples include at least one or a combination of lithium nickel oxides, lithium cobalt oxides, lithium manganese oxides, cobalt-free lithium nickel manganese oxides, and lithium manganese-rich composite oxides. This positive electrode active material can be mixed with the aforementioned lithium iron phosphate positive electrode active material and coated onto the positive electrode. Based on a 100 wt% positive electrode active material layer, the amount of positive electrode active material can be, for example, from about 1 wt% to about 40 wt%, or from about 5 wt% to about 20 wt%.

[0036] The positive electrode active material layer may further include a binder and / or a conductive material.

[0037] The binder improves the adhesion properties between the positive electrode active material particles and between the positive electrode active material particles and the current collector. Examples of binders may include, but are not limited to, at least one of the following: polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylate resin, polyester resin, and nylon. Based on 100 wt% of the positive electrode active material layer, the amount of binder may be from about 0.1 wt% to about 5 wt%.

[0038] Conductive materials may be included to provide electrode conductivity, and any conductive material may be conductive unless it causes a chemical change in the battery. Examples of conductive materials may include: carbon-based materials, such as at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers, carbon nanotubes, etc.; metallic materials of the form of metal powders or fibers, including at least one of copper, nickel, aluminum, silver, etc.; conductive polymers, such as polyphenylene derivatives; or mixtures thereof. Based on a 100 wt% positive electrode active material layer, the amount of conductive material may be from about 0.1 wt% to about 5 wt%.

[0039] There are no particular restrictions on the positive electrode current collector, as long as it is conductive and does not cause chemical changes in the rechargeable lithium battery, and it can be or include an aluminum foil with a thickness of about 10 μm to about 15 μm.

[0040] The positive electrode can be manufactured using conventional methods for manufacturing positive electrodes. For example, the positive electrode can be manufactured by mixing a positive electrode active material and optionally a binder and / or a conductive material in a solvent to prepare a positive electrode active material slurry, coating the positive electrode active material slurry onto a positive electrode current collector, and then drying and pressing it.

[0041] The solvent can be or includes common solvents, such as at least one of dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone, or water, and can be used alone or in mixtures of two or more. The amount of solvent is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, taking into account the coating thickness and manufacturing yield, and is sufficient at the time of coating to have a viscosity that can exhibit desired or advantageous thickness uniformity for subsequent positive electrode fabrication.

[0042] Because the density, porosity, pore size, and thickness of the mixture can vary depending on the loading level, drying conditions, and pressing conditions of the positive electrode active material layer, it is necessary to appropriately adjust the loading level, drying conditions, and pressing conditions of the positive electrode active material layer.

[0043] There is no particular limitation on the loading level of the positive electrode active material layer per unit area of ​​the positive electrode current collector, but it can be, for example, about 20 mg / cm². 2 Approximately 50 mg / cm 2 The loading level of the positive electrode active material layer per unit area of ​​the positive electrode current collector can be approximately 25 mg / cm². 2 Approximately 45 mg / cm 2 Approximately 30 mg / cm 2 Approximately 40 mg / cm 2 or approximately 35 mg / cm³ 2 Approximately 40 mg / cm 2 .

[0044] Drying can be carried out at a temperature of about 100°C to about 180°C. Drying can be carried out at a constant temperature or by increasing (e.g., sequentially increasing) the temperature. When drying is carried out by increasing (e.g., sequentially increasing) the temperature, the drying can be divided into two to four steps. According to some example embodiments, drying can be carried out in, for example, four steps, and the drying temperature for each step can be about 138°C, about 142°C, about 145°C, and about 150°C, but is not limited thereto.

[0045] Pressing can be performed using pressure rollers at a temperature of approximately 20°C to approximately 25°C. The temperature of the pressure rollers can be adjusted appropriately according to the intended purpose.

[0046] During pressing, the pressing line pressure can be from about 0.5 ton / cm to about 1 ton / cm. The pressing line pressure can be greater than or equal to about 0.55 ton / cm, greater than or equal to about 0.6 ton / cm, greater than or equal to about 0.65 ton / cm, greater than or equal to about 0.7 ton / cm, greater than or equal to about 0.75 ton / cm, or greater than or equal to about 0.8 ton / cm, and less than or equal to about 0.99 ton / cm, less than or equal to about 0.98 ton / cm, less than or equal to about 0.97 ton / cm, less than or equal to about 0.96 ton / cm, or less than or equal to about 0.95 ton / cm. By adjusting the pressing line pressure within the above range during pressing, pressing can be controlled to achieve the desired mixture density, and therefore pressing can be adjusted to have the desired porosity and pore size of the positive electrode.

[0047] The mixture density of the positive electrode active material layer formed under pressing conditions (especially pressing pipeline pressure) can be from about 1 g / cc to about 2.69 g / cc. The mixture density refers to the weight per unit volume of the positive electrode active material layer on the current collector in the positive electrode. For example, the mixture density of the positive electrode active material layer can be greater than or equal to about 1.5 g / cc, greater than or equal to about 2 g / cc, greater than or equal to about 2.1 g / cc, greater than or equal to about 2.2 g / cc, and less than or equal to about 2.65 g / cc, less than or equal to about 2.6 g / cc, less than or equal to about 2.55 g / cc, less than or equal to about 2.5 g / cc, or less than or equal to about 2.45 g / cc. By adjusting the mixture density of the positive electrode active material layer to any of the above ranges, capacity and energy density can be increased, and fast charging characteristics can be improved by satisfying the porosity and pore size of the positive electrode as described above.

[0048] The thickness of the positive electrode active material layer can be from approximately 145 μm to approximately 180 μm. For example, the thickness of the positive electrode active material layer can be from approximately 147 μm to approximately 178 μm, from approximately 150 μm to approximately 178 μm, or from approximately 155 μm to approximately 175 μm. The thickness of the positive electrode active material layer can be measured by SEM images of the cross-section of the pressed positive electrode. When the thickness of the positive electrode active material layer meets any of the above ranges, capacity and energy density can be improved, and simultaneously, fast charging characteristics can be improved by adjusting the pore size and porosity within the positive electrode.

[0049] negative electrode The negative electrode according to some example embodiments includes a carbonaceous negative electrode active material. For example, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector and including the carbonaceous negative electrode active material.

[0050] The carbonaceous negative electrode active material may include crystalline carbon, amorphous carbon, or a combination thereof. The crystalline carbon may be natural graphite or artificial graphite that is irregular, or in the form of flakes, lamellae, spheres, or fibers. The amorphous carbon may be or include at least one of soft carbon, hard carbon, mesophase pitch carbonized product, calcined coke, etc. Soft carbon refers to a carbon material that can be graphitized and is a material that can be easily graphitized by heat treatment at a high temperature (e.g., at about 2800 °C). Hard carbon is or includes a carbon material that cannot be graphitized, or a carbon material that is finely graphitized by heat treatment.

[0051] The negative electrode active material layer may further include other types of negative electrode active materials in addition to the carbonaceous negative electrode active material, and may further include at least one of, for example, lithium metal, lithium metal alloy, and a material capable of doping and de-doping lithium.

[0052] The lithium metal alloy includes an alloy of lithium and a metal such as or including at least one of Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.

[0053] The material capable of doping / dedoping lithium may be or include a Si-based negative electrode active material or a Sn-based negative electrode active material. The Si-based negative electrode active material may include silicon, a silicon-carbon composite, SiO x (0 < x ≤ 2), a Si-Q alloy (where Q is an element such as or including at least one of an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element (excluding Si), a Group 15 element, a Group 16 element, a transition metal, a rare earth element, and a combination thereof), or a combination of at least one of them. The Sn-based negative electrode active material may be or include at least one of Sn, SnO2, a Sn-based alloy, or a combination thereof.

[0054] The silicon-carbon composite may be or include a composite of silicon and amorphous carbon. According to some example embodiments, the silicon-carbon composite may be in the form of silicon particles and amorphous carbon coated on the surface of the silicon particles. For example, the silicon-carbon composite may include secondary particles (cores) aggregated from silicon primary particles and an amorphous carbon coating (shell) on the surface of the secondary particles. Amorphous carbon may also be present between the silicon primary particles, for example, the silicon primary particles may be coated with amorphous carbon. The secondary particles may be dispersed in an amorphous carbon matrix.

[0055] The silicon-carbon composite may further include crystalline carbon. For example, the silicon-carbon composite may include a core comprising crystalline carbon and silicon particles, and an amorphous carbon coating on the surface of the core.

[0056] Si-based or Sn-based negative electrode active materials can be mixed with carbon-based negative electrode active materials.

[0057] Based on a 100wt% negative electrode active material layer, the amount of negative electrode active material can be from about 90wt% to about 99.8wt% or from about 94wt% to about 99wt%.

[0058] The negative electrode active material layer may further include a binder and / or a conductive material. The binder is configured to ensure sufficient adhesion between the negative electrode active material particles and also to the current collector. The binder may be or include at least one of a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof.

[0059] Non-aqueous adhesives may include at least one of polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene-propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyimide, or combinations thereof.

[0060] Waterborne adhesives may include at least one of the following: styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepoxychloropropane, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, or combinations thereof.

[0061] When the aqueous binder is a negative electrode binder, it may further include a cellulose-based compound capable of imparting viscosity. As a cellulose-based compound, one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, or their alkali metal salts may be mixed and used. The alkali metal may be or include at least one of Na, K, or Li.

[0062] The dry binder may be or include a polymeric material capable of being converted into fibers, and may be or include at least one of, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or combinations thereof. Based on a 100 wt% negative electrode active material layer, the amount of binder may be from about 0.1 wt% to about 5 wt%, or from about 0.5 wt% to about 3 wt%.

[0063] The conductive material is included to provide electrode conductivity, and any conductive material may be conductive unless it causes a chemical change in the battery. Examples of conductive materials include: carbon-based materials, such as or including at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers, carbon nanotubes, etc.; metallic materials, such as metal powders or metal fibers, including at least one of copper, nickel, aluminum, silver, etc.; conductive polymers, such as polyphenylene derivatives; or mixtures thereof. Based on a 100 wt% negative electrode active material layer, the amount of conductive material may be from about 0.1 wt% to about 5 wt%, or from about 0.5 wt% to about 3 wt%.

[0064] There are no particular restrictions on the negative electrode current collector, as long as it is conductive and does not cause chemical changes in the rechargeable lithium battery, and it can be a copper foil with a thickness of about 10 μm to about 15 μm.

[0065] Methods for manufacturing a negative electrode may include, for example, mixing a negative electrode active material and optional binder and / or conductive material in a solvent to prepare a negative electrode active material slurry, coating the negative electrode active material slurry onto a negative electrode current collector, and then drying and pressing it.

[0066] The solvent may be of the same type as the solvent included in the positive electrode active material slurry, or may be or include an aqueous solvent.

[0067] According to some example embodiments, the negative electrode has a value less than or equal to about 20 Ωcm. 2 The ionic resistance. For example, the ionic resistance of the negative electrode can be less than or equal to about 20 Ωcm. 2 Less than or equal to approximately 19.5 Ωcm 2 Less than or equal to approximately 19 Ωcm 2 Or less than or equal to approximately 18.8 Ωcm 2 The lower limit of the ionic resistance of the negative electrode is not limited, but it can be greater than or equal to approximately 15 Ωcm. 2 ≥15.5Ωcm 2 ≥16Ωcm 2 ≥16.5Ωcm 2 ≥17Ωcm 2 or greater than or equal to 17.6 Ωcm 2The ionic resistance of the negative electrode can be measured as follows: For example, a symmetrical cell consisting of two negative electrodes is fabricated, the amplitude Va is set to 5 mV, SC-EIS (square-wave current electrochemical impedance spectroscopy) is measured, and the ionic resistance is measured using transmission line model theory to isolate only the ion-moving resistance within the internal resistance of the negative electrode. The ionic resistance of the negative electrode refers to the ion-moving resistance within the internal resistance of the active material layer of the negative electrode. In some example embodiments, the ionic resistance of the negative electrode, which includes a carbon-based negative electrode active material, is designed to be less than or equal to about 20 Ωcm. 2 This can improve fast charging and discharging performance and output characteristics. The ionic resistance of the negative electrode can be adjusted to less than or equal to approximately 20 Ωcm by regulating the type of active material, the loading level of the active material layer, and the drying and pressing conditions of the negative electrode (e.g., pressing line pressure). 2 The range.

[0068] As mentioned above, the ionic resistance of the negative electrode can vary depending on the loading level of the negative electrode active material layer, drying conditions, and pressing conditions. Therefore, it is necessary to appropriately adjust the loading level, drying conditions, and pressing conditions (e.g., pressing line pressure) of the negative electrode active material layer.

[0069] There is no particular limitation on the loading level of the negative electrode active material layer per unit area of ​​the negative electrode current collector, but it can be, for example, about 10 mg / cm². 2 Approximately 35 mg / cm 2 The loading level of the negative electrode active material layer per unit area of ​​the negative electrode current collector can be approximately 15 mg / cm². 2 Approximately 30 mg / cm 2 Approximately 20 mg / cm 2 Approximately 30 mg / cm 2 or approximately 20 mg / cm³ 2 Approximately 25 mg / cm 2 .

[0070] Drying can be carried out at a temperature of about 20°C to about 120°C. For example, the drying temperature can be greater than or equal to about 30°C, greater than or equal to about 40°C, greater than or equal to about 50°C, greater than or equal to about 60°C, or greater than or equal to about 70°C, and can be less than or equal to about 110°C, less than or equal to about 100°C, less than or equal to about 90°C, less than or equal to about 80°C, or less than or equal to about 70°C. Because the ionic resistance of the negative electrode increases with increasing drying temperature or drying speed, the drying temperature can be adjusted within the above range during the manufacture of the negative electrode to ensure that the ionic resistance of the negative electrode is within the above range.

[0071] In addition to pressing the pipeline pressure, pressing can be performed under the same conditions as when pressing the positive electrode.

[0072] The pressing line pressure during pressing can be from about 0.01 ton / cm to about 0.1 ton / cm. The pressing line pressure can be greater than or equal to about 0.02 ton / cm, greater than or equal to about 0.03 ton / cm, greater than or equal to about 0.04 ton / cm, or greater than or equal to about 0.05 ton / cm, and can be less than or equal to about 0.099 ton / cm, less than or equal to about 0.098 ton / cm, less than or equal to about 0.097 ton / cm, less than or equal to about 0.096 ton / cm, less than or equal to about 0.095 ton / cm, or less than or equal to about 0.094 ton / cm. By adjusting the pressing line pressure within any of the above ranges during pressing, the pressing line pressure can be controlled to achieve a desired mixture density, and therefore the pressing line pressure can be adjusted to have a desired ionic resistance of the negative electrode.

[0073] The mixture density of the negative electrode active material layer formed under the pressing conditions (especially the pressing pipeline pressure) can be from about 1 g / cc to about 1.59 g / cc. The mixture density refers to the weight per unit volume of the negative electrode active material layer on the current collector in the negative electrode. For example, the mixture density of the negative electrode active material layer can be greater than or equal to about 1.1 g / cc, greater than or equal to about 1.2 g / cc, greater than or equal to about 1.3 g / cc, greater than or equal to about 1.4 g / cc, or greater than or equal to about 1.43 g / cc, and can be less than or equal to about 1.58 g / cc, less than or equal to about 1.57 g / cc, less than or equal to about 1.56 g / cc, less than or equal to about 1.55 g / cc, less than or equal to about 1.54 g / cc, or less than or equal to about 1.53 g / cc. By adjusting the mixture density of the negative electrode active material layer to the above range, the ionic resistance value of the negative electrode can be satisfied, and high stability, high capacity, and fast charging characteristics can be ensured when assembled with the positive electrode.

[0074] The thickness of the negative electrode active material layer can be from about 100 μm to about 200 μm. For example, the thickness of the negative electrode active material layer can be greater than or equal to about 105 μm, greater than or equal to about 110 μm, greater than or equal to about 115 μm, greater than or equal to about 120 μm, or greater than or equal to about 125 μm, and can be less than or equal to about 145 μm, less than or equal to about 140 μm, less than or equal to about 135 μm, or less than or equal to about 130 μm. As the negative electrode active material layer becomes thicker, the capacity can be increased, but the ionic resistance of the negative electrode increases. As the negative electrode active material layer becomes thinner, the ionic resistance of the negative electrode decreases, but the capacity decreases. However, in some example embodiments, by appropriately adjusting the pressing conditions (e.g., pressing line pressure), the mixture density of the negative electrode active material layer can be adjusted within an appropriate range, thereby controlling the thickness of the negative electrode active material layer to ensure that the ionic resistance is within the aforementioned range, and ensuring high capacity and fast charging characteristics.

[0075] electrolytes For example, the electrolyte used in a rechargeable lithium battery may be or include an electrolyte containing a non-aqueous organic solvent and a lithium salt.

[0076] Non-aqueous organic solvents can serve as media for transporting ions that participate in the electrochemical reactions of a battery.

[0077] Non-aqueous organic solvents may be or include at least one of carbonate solvents, ester solvents, ether solvents, ketone solvents or alcohol solvents, aprotic solvents or combinations thereof.

[0078] Carbonate solvents may include at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), and butyl carbonate (BC). Ester solvents may include at least one of methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanolactone, mevalonolactone, valproic acid lactone, and caprolactone. Ether solvents may include at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, and tetrahydrofuran. Additionally, ketone solvents may include cyclohexanone. Alcohol solvents may include at least one of ethanol, isopropanol, etc., and aprotic solvents may include at least one of nitriles (such as R-CN (where R is a C2 to C20 straight-chain, branched or cyclic hydrocarbon group, and includes double bonds, aromatic rings or ether groups, etc.)), amides (such as dimethylformamide), dioxolane (such as 1,3-dioxolane, 1,4-dioxolane, etc.), sulfolane, etc.

[0079] Non-aqueous organic solvents can be used alone or in mixtures of two or more solvents.

[0080] When using carbonate solvents, cyclic carbonates and chain carbonates can be mixed and used, and cyclic carbonates and chain carbonates can be mixed in a volume ratio of about 1:1 to about 1:9.

[0081] Lithium salts dissolved in organic solvents supply lithium ions in batteries, enabling basic operation of rechargeable lithium batteries and improving lithium ion transport between the positive and negative electrodes. Examples of lithium salts can include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 At least one of the following: (SO2) (where x and y are integers from 1 to 20), lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalate)phosphate (LiDFBOP), and lithium bis(oxalate)borate (LiBOB).

[0082] diaphragm Depending on the type of rechargeable lithium battery, a separator can be present between the positive and negative electrodes. The separator can include at least one of polyethylene, polypropylene, polyvinylidene fluoride, or a multilayer membrane of two or more layers thereof, as well as mixed multilayer membranes, such as polyethylene / polypropylene two-layer separators, polyethylene / polypropylene / polyethylene three-layer separators, polypropylene / polyethylene / polypropylene three-layer separators, etc.

[0083] The membrane may include a porous substrate and a coating on one or both surfaces of the porous substrate, comprising organic materials, inorganic materials or combinations thereof.

[0084] The porous substrate may be or comprise a polymer membrane formed of or containing any polymer, said polymer including polyolefins (such as or including at least one of polyethylene and polypropylene), polyesters (such as polyethylene terephthalate and polybutylene terephthalate), polyacetal, polyamide, polyimide, polycarbonate, polyetherketone, polyaryletherketone, polyetherketone, polyetherimide, polyamideimide, polybenzimidazole, polyethersulfone, polyphenylene ether, cyclic olefin copolymers, polyphenylene sulfide, polyethylene naphthalate, glass fiber, and polytetrafluoroethylene (e.g., TEFLON). ® ( ), or copolymers or mixtures of two or more thereof.

[0085] Organic materials may include polymers such as polyvinylidene fluoride or (meth)acrylic acid polymers.

[0086] Inorganic materials may include, but are not limited to, inorganic particles such as or including at least one of Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and combinations thereof.

[0087] Organic and inorganic materials can be mixed in a coating, or coatings containing organic materials and coatings containing inorganic materials can be stacked.

[0088] Rechargeable lithium batteries A rechargeable lithium battery according to some example embodiments includes the above-described positive electrode, negative electrode, and electrolyte.

[0089] Rechargeable lithium batteries can exhibit fast-charging characteristics by including the aforementioned positive and negative electrodes. If the charge level is greater than or equal to approximately 80% after charging at a constant current of 1.68C for 25 minutes at 25°C, the fast-charging characteristic can be considered successful.

[0090] In other words, when charged at a constant current of 1.68C for 25 minutes at 25°C, a rechargeable lithium battery can have a charge capacity of more than or equal to about 80%.

[0091] Furthermore, when a rechargeable lithium battery is charged at a constant current of 1.68C for 25 minutes at 25°C and discharged once at 0.05C, analysis based on the voltage diagram of capacity during discharge shows that, based on a 100wt% negative electrode active material layer, the amount of lithium deposited on the negative electrode surface can be less than or equal to about 1wt%. For example, the amount of lithium deposited can be less than or equal to about 0.99wt%, less than or equal to about 0.95wt%, or less than or equal to about 0.90wt%. The lower limit of the amount of lithium deposited is not limited, but it can be greater than or equal to 0wt%. Rechargeable lithium batteries according to some example embodiments can improve fast-charging characteristics by enabling smooth lithium-ion movement while achieving high capacity, and even under fast-charging conditions, desired or advantageous performance can be achieved due to the small amount of lithium deposited on the negative electrode surface.

[0092] A rechargeable lithium battery may include a positive electrode, a negative electrode, a separator between the positive and negative electrodes, and an electrolyte.

[0093] Some example embodiments include an all-solid-state rechargeable battery comprising a positive electrode, a negative electrode, and a solid electrolyte layer between the positive and negative electrodes.

[0094] For convenience, the construction of lithium-ion batteries using liquid electrolytes will be described in detail below.

[0095] Rechargeable lithium batteries can be classified according to their shape, such as cylindrical, prismatic, pouch-shaped, and coin-shaped. Figures 1 to 4 This is a schematic diagram illustrating a rechargeable lithium battery according to some example embodiments, wherein, Figure 1 It is a cylindrical battery. Figure 2 It is a prismatic battery. Figure 3 and Figure 4 It's a pouch battery. (See reference) Figures 1 to 4 The rechargeable lithium battery 100 includes an electrode assembly 40 having a separator 30 disposed between a positive electrode 10 and a negative electrode 20, and a housing 50 therein housing the electrode assembly 40. The positive electrode 10, negative electrode 20, and separator 30 may be impregnated with an electrolyte (not shown). Figure 1 As shown, the rechargeable lithium battery 100 may include a sealing member 60 of the sealed housing 50. Additionally, in Figure 2 In this context, the rechargeable lithium battery 100 may include a positive electrode lead connector 11, a positive electrode terminal 12, a negative electrode lead connector 21, and a negative electrode terminal 22. For example... Figure 3 and Figure 4 As shown, the rechargeable lithium battery 100 includes Figure 4 The electrode terminals 70 shown in the figure and Figure 3The positive electrode terminal 71 and negative electrode terminal 72 shown in the figure form an electrical path for guiding the current generated in the electrode assembly 40 to the outside of the rechargeable lithium battery 100.

[0096] Examples and comparative examples of this disclosure are described below. However, the following examples are merely examples of this disclosure, and this disclosure is not limited to these examples.

[0097] Examples and Comparison Examples The positive electrode and the rechargeable lithium battery cell are manufactured in the following manner.

[0098] Example 1 (1) Manufacturing of the positive electrode The average particle size (D) of the active material for the positive electrode will be used as the average particle size. 50 A positive electrode active material composition was prepared by mixing 1.07 μm LiFePO4, polyvinylidene fluoride as a binder, and carbon nanotubes as a conductive material in a weight ratio of 96.36:2.44:1.2 (positive electrode active material: binder: conductive material). This positive electrode active material composition was dispersed in N-methylpyrrolidone solvent to prepare a positive electrode active material slurry, which was then mixed at a concentration of 39.13 mg / cm³. 2 The loading level was coated onto Al foil to a thickness of 14 μm, followed by drying and pressing in four steps at 138 °C, 142 °C, 145 °C, and 150 °C to fabricate the positive electrode. Pressing was performed with rollers at approximately 25 °C while controlling the pressing line pressure to approximately 0.83 ton / cm.

[0099] Here, after pressing, the positive electrode has a mixture density of about 2.23 g / cc, its positive electrode active material layer has a thickness of about 174 μm, and the pores in the positive electrode, measured by the mercury intrusion method, have a size of about 0.86 μm and a porosity of about 33%.

[0100] (2) Manufacturing of the negative electrode A negative electrode active material slurry was prepared by dispersing 97.5 wt% graphite as the negative electrode active material, 1.5 wt% carboxymethyl cellulose as a binder, and 1 wt% styrene-butadiene rubber in distilled water. The negative electrode active material slurry was then subjected to a concentration of 22.85 mg / cm³. 2 The loading level was coated onto an 8 μm thick Cu foil, then dried at 70 °C and pressed to fabricate the negative electrode. Here, the pressing was performed in the same manner as in the fabrication of the positive electrode, except that the pressing line pressure was changed to 0.0563 ton / cm.

[0101] Here, after pressing, the negative electrode has a mixture density of approximately 1.42 g / cc, and its negative electrode active material layer has a thickness of approximately 163 μm, and the negative electrode has an Ωcm of approximately 18.8 Ω. 2 The ionic resistance.

[0102] (3) Manufacturing of rechargeable lithium battery cells An electrode assembly was fabricated by inserting a 10 μm thick polyethylene separator between the positive and negative electrodes. This assembly was then inserted into a housing and an electrolyte was injected, thus creating a rechargeable lithium-ion battery cell (a 100 mAh-class pouch cell). An electrolyte was prepared by mixing EC (ethylene carbonate), EMC (ethyl methyl carbonate), and DMC (dimethyl carbonate) in a 2:4:4 volume ratio and dissolving 1.15 M LiPF6 in the mixed solvent.

[0103] Example 2 The positive electrode, negative electrode, and rechargeable lithium battery cell are manufactured in essentially the same manner as in Example 1, except that the pressing line pressure is changed to 0.92 ton / cm in the manufacture of the positive electrode.

[0104] Here, after pressing, the positive electrode has a mixture density of 2.38 g / cc, the positive electrode active material layer of the positive electrode has a thickness of about 162 μm, and the pores of the positive electrode, as measured by mercury intrusion porosimetry, have a size of about 0.69 μm and a porosity of about 28%.

[0105] Example 3 The positive electrode, negative electrode, and rechargeable lithium battery cell are manufactured in essentially the same manner as in Example 1, except that the pressing line pressure is changed to 0.95 ton / cm in the manufacture of the positive electrode.

[0106] Here, after pressing, the positive electrode has a mixture density of 2.44 g / cc, the positive electrode active material layer of the positive electrode has a thickness of about 156 μm, and the pores in the positive electrode, as measured by mercury intrusion porosimetry, have a size of about 0.63 μm and a porosity of about 25%.

[0107] Example 4 The positive electrode, negative electrode, and rechargeable lithium battery cell are manufactured in essentially the same manner as in Example 1, except that the pressing line pressure is changed to 0.0934 ton / cm during the manufacture of the negative electrode.

[0108] Here, after pressing, the negative electrode has a mixture density of 1.53 g / cc, the negative electrode active material layer has a thickness of approximately 152 μm, and the negative electrode has an Ωcm of approximately 17.6.2 The ionic resistance.

[0109] Comparison Example 1 The positive electrode, negative electrode, and rechargeable lithium battery cell are manufactured in essentially the same manner as in Example 1, except that the pressing pipeline pressure is changed to 1.1 ton / cm in the manufacture of the positive electrode.

[0110] Here, after pressing, the positive electrode has a mixture density of 2.7 g / cc, the positive electrode active material layer of the positive electrode has a thickness of about 145 μm, and the pores in the positive electrode, as measured by mercury intrusion porosimetry, have a size of about 0.55 μm and a porosity of about 22%.

[0111] Comparison Example 2 The positive electrode, negative electrode, and rechargeable lithium battery cell are manufactured in essentially the same manner as in Example 1, except that the pressing line pressure is changed to 0.1046 ton / cm in the manufacture of the negative electrode.

[0112] Here, after pressing, the negative electrode has a mixture density of 1.6 g / cc, the negative electrode active material layer has a thickness of approximately 146 μm, and the negative electrode has an Ωcm of approximately 21.2. 2 The ionic resistance.

[0113] The load level, drying temperature, roller temperature, pressing line pressure, and mixture density of each positive electrode in Examples 1 to 4 and Comparative Examples 1 to 2, as well as the load level, drying temperature, roller temperature, pressing line pressure, and mixture density of each negative electrode, are summarized in Table 1.

[0114] Table 1:

[0115] Evaluation Example 1: Pore characteristics of the positive electrode and ion resistance characteristics of the negative electrode The pore size and porosity of the positive electrodes according to Examples 1 to 4 and Comparative Examples 1 to 2 were measured by mercury intrusion porosimetry. Mercury was introduced into the pores of each sample by utilizing the unique property of mercury as a non-wetting solid, and a pressure of 360,000 to 361,727 psia was applied to measure the amount of mercury introduced using a mercury porosimeter. This was used to measure the total pore volume, pore size, pore surface area, etc. The results are shown in Table 2.

[0116] Subsequently, the ion resistance of the negative electrodes of Examples 1 to 4 and Comparative Examples 1 to 2 were measured respectively. A symmetrical cell consisting of two negative electrodes was fabricated and subjected to SC-EIS (square wave current electrochemical impedance spectroscopy) at an amplitude Va of 5 mV. The measurement results were analyzed using transmission line model theory to separate the individual ion migration resistance (Rion) within the internal resistance of the negative electrode, and thus the ion resistance was obtained. The results are shown in Table 2.

[0117] Table 2:

[0118] Evaluation Example 2: Evaluation of Fast Charging Features The rechargeable lithium-ion battery cells of Examples 1 to 4 and Comparative Examples 1 to 2 were charged at a constant current of 1.68C for 25 minutes at 25°C to obtain the charge amount used to evaluate the fast charging characteristics.

[0119] The results are shown in Table 3.

[0120] Evaluation criteria: -Charge capacity greater than or equal to 80%: O -Charge level less than 80%: Failure Table 3:

[0121] Evaluation Example 3: Evaluation of Lithium Deposition Amount The rechargeable lithium battery cells of Examples 1 to 4 and Comparative Examples 1 to 2 were immediately and continuously discharged at 0.05C after the fast charging evaluation of Example 2 (charged at a constant current of 1.68C for 25 minutes at 25°C) to obtain voltage curves based on capacity. Then, the area under the curve for the inflection point was calculated to obtain the amount of lithium deposited, and the results are shown in Table 4.

[0122] Table 4:

[0123] Summarize Referring to Table 3 based on Evaluation Example 2, it is confirmed that Examples 1 to 4 exhibit fast charging characteristics.

[0124] Referring to Table 4 of Evaluation Example 3, Examples 1 to 4 and Comparative Example 1 exhibited a lithium deposition of less than 1 wt% during fast charging. Due to the low lithium deposition, higher rate capability and desired or favorable lifetime cycle characteristics can be achieved during fast charging and discharging.

[0125] However, Comparative Example 1 failed in the fast charging characteristic evaluation, which confirms that the design of the positive and negative electrodes should be appropriately adjusted in order to ensure 1 wt% lithium deposition and meet the fast charging characteristics.

[0126] For example, Comparative Example 1, where the negative electrode has an ion resistance within the expected range but the positive electrode has porosity and pore size outside the expected range, satisfies a lithium deposition of less than 1 wt% but does not meet the fast charging characteristics. Comparative Example 2, where the positive electrode has porosity and pore size within the expected range but the negative electrode has an ion resistance outside the expected range, does not meet the fast charging characteristics and exhibits a lithium deposition of not less than 1 wt% at 1.4 wt%.

[0127] On the other hand, the rechargeable lithium battery cells of Examples 1 to 4 meet the requirements of fast charging characteristics and less than 1 wt% lithium deposition, which indicates that in order to ensure fast charging characteristics and less than 1 wt% lithium deposition, the porosity and pore size of the positive electrode and the ionic resistance of the negative electrode should be adjusted within the desired range.

[0128] In addition, in order to achieve the desired porosity and pore size of the positive electrode and meet the ion resistance of the negative electrode, it was confirmed that the density of the positive electrode mixture and the density of the negative electrode mixture were adjusted to meet the desired range.

[0129] While this disclosure has been described in conjunction with exemplary embodiments now considered to be practical, it will be understood that the disclosure is not limited to the disclosed exemplary embodiments, but rather is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.

[0130] Explanation of reference numerals in the attached figures: 100: Rechargeable lithium battery 10: Positive electrode 11: Positive electrode lead connector 12: Positive electrode terminal 20: Negative electrode 21: Negative electrode lead connector 22: Negative electrode terminal 30: Diaphragm 40: Electrode assembly 50: Casing 60: Sealing component 70: Electrode connector 71: Positive electrode connector 72: Negative electrode connector.

Claims

1. A rechargeable lithium battery, said rechargeable lithium battery comprising: A positive electrode includes a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer includes a lithium iron phosphate-based positive electrode active material; A negative electrode includes a negative electrode current collector and a negative electrode active material layer on the negative electrode current collector, wherein the negative electrode active material layer comprises a carbon-based negative electrode active material; as well as Electrolytes, The positive electrode includes a hole with a size of 0.6 μm to 1 μm. The positive electrode has a porosity greater than or equal to 23%, and The negative electrode has a strength of less than or equal to 20 Ωcm. 2 The ionic resistance.

2. The rechargeable lithium battery according to claim 1, wherein, The lithium iron phosphate positive electrode active material is represented by one of chemical formulas 1 and 2: Chemical Formula 1: Li a1 Fe (1-x1) M 1 x1 PO4 In chemical formula 1, 0.90 ≤ a1 ≤ 1.5, 0 ≤ x1 ≤ 0.4, and M 1 Including at least one of Al, B, Ca, Ce, Cr, Cu, La, Mg, Mn, Mo, Nb, Ni, Si, Sn, Sr, Ti, V, W, Y, Zn, and Zr; Chemical formula 2: Li a2 Mn x2 Fe (1-x2-y2) M 2 y2 PO4 In chemical formula 2, 0.90 ≤ a² ≤ 1.5, 0.1 ≤ x² ≤ 0.9, 0 ≤ y² ≤ 0.9, and M 2 It includes at least one of Al, B, Ca, Ce, Cr, Cu, La, Mg, Mo, Nb, Ni, Si, Sn, Sr, Ti, V, W, Y, Zn, and Zr.

3. The rechargeable lithium battery according to claim 1, wherein, The lithium iron phosphate positive electrode active material has an average particle size of 0.01 μm to 4 μm.

4. The rechargeable lithium battery according to claim 1, wherein, The positive electrode has a porosity of 23% to 50%.

5. The rechargeable lithium battery according to claim 1, wherein, The positive electrode active material layer has a mixture density of 1 g / cc to 2.69 g / cc.

6. The rechargeable lithium battery according to claim 1, wherein, The positive electrode active material layer has a thickness of 145 μm to 180 μm.

7. The rechargeable lithium battery according to claim 1, wherein, Based on the 100wt% positive electrode active material layer, the amount of the lithium iron phosphate positive electrode active material is from 60wt% to 99.9wt%.

8. The rechargeable lithium battery according to claim 1, wherein: The positive electrode active material layer also includes a binder and a conductive material. Based on the 100wt% positive electrode active material layer, the amount of the binder is 0.1wt% to 5wt%, and Based on the 100wt% positive electrode active material layer, the amount of the conductive material is from 0.1wt% to 5wt%.

9. The rechargeable lithium battery according to claim 1, wherein, The negative electrode has a 15Ωcm 2 Up to 20Ωcm 2 The ionic resistance.

10. The rechargeable lithium battery according to claim 1, wherein, The negative electrode active material layer has a mixture density of 1 g / cc to 1.59 g / cc.

11. The rechargeable lithium battery according to claim 1, wherein, The negative electrode active material layer has a thickness of 100 μm to 200 μm.

12. The rechargeable lithium battery according to claim 1, wherein, When charged at a constant current of 1.68C for 25 minutes at 25°C, the charge is greater than or equal to 80%.

13. The rechargeable lithium battery according to claim 1, wherein, When charged at a constant current of 1.68C for 25 minutes at 25°C and discharged once at 0.05C, analysis based on the voltage diagram of capacity during discharge showed that the amount of lithium deposited on the surface of the negative electrode was less than or equal to 1wt% based on a 100wt% negative electrode active material layer.